(untitled) (Global Journal of Management and Business Research, 2021)
The German banking industry is facing major challenges due to digitalization. The digital transformation is significantly influenced by technological progress, tighter regulation and low-interest phases. The market entry of fintechs and changing customer behaviour is also a reality. To meet the challenge of the digitalization and to to reduce costs, savings banks are increasingly turning to mergers, staff cuts and branch closures. The purpose of this research is to investigate the impact of digitalization on German savings banks. Through an explorative literature review, scientific sources and real KPIs of savings banks in Germany were used. The impact of digitalization on savings banks in the period 1999 -2018 was investigated using the study situation and the analysis of key business figures. The aim is to answer whether the costcutting actions of savings banks are justified from an economic point of view based on the KPIs operating result, cost-income ratio and return on equity. In recent years, it has become clear that German banks lack a clear strategy. The results may be of interest to researchers dealing with the digital transformation of savings banks in Germany.